(untitled) (Marketing Journal, 2025)
This article analyzes the modern mechanisms for the functioning and development of small businesses in the service sector of the region. In addition, the decrees and resolutions issued by the head of our country on the development of the industry, the measures aimed at developing entrepreneurship in the development strategy and the tasks set, as well as their content and essence, are highlighted, and scientific recommendations are given.